Peningkatan Berpikir Kritis pada Mata Pelajaran Sejarah Melalui Pendekatan Pembelajaran Konstruktivistik - Rudi Hermanto (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2016)
This study aims to determine the effect of constructivist learning approach on improving critical thinking skills and learning outcomes of learners history . The method used in this study is action research method to the design of the spiral model Kemmis and Taggart . The instruments used are the guidelines for the observation of critical thinking skills and learn the history of the test results . Subjects were students of class XII IPS 3 SMA Negeri 42 Jakarta totaling 33 people . The results are: (1) Application of constructivist learning approach can improve critical thinking skills and learning outcomes of the History of learners ; (2) Planting material concepts through constructivist learning model can accelerate and facilitate the understanding of the learners; (3) Through the constructivist learning approach learners are becoming increasingly active in finding and exploring new knowledge; (4) In the process constructivist learning approach to attract learners in studying the history lesson .